Fabrication of PZT Thick Film by Electrophoretic Deposition on the Platinum Substrate - Ngo, Truong Ngoc Mai; Iasmi , Sterianou; Ian, Reaney; Luong, Huynh Vu Thanh; Cao, Luu Ngoc Hanh; Dang, Huynh Giao (CTU Journal of Innovation and Sustainable Development, 2022)
PbZrxTi1-xO3 compositions near morphotropic phase boundary have been reported to have high piezoelectric properties. In this study, Pb(Zr0.5Ti0.5)O3 (PZT 50/50) powder was produced by the solid-state reaction from the relevant oxides at 950oC. Phase analysis using X-ray diffraction revealed the single phase of the tetragonal perovskite structure. PZT thick film was fabricated by electrophoretic deposition of the resulted PZT powder onto the Pt substrate. The electrophoretic deposition process was conducted in an ethanol medium, and the effects of deposition parameters such as pH, applied voltage and deposition time on the film thickness were investigated. A green film with a maximum thickness of ~95 μm and sintered film with a maximum thickness of 80±2 μm were prepared. The effects of sintering atmosphere and temperatures on phase transformation and microstructures of PZT film were evaluated using X-ray diffraction and scanning electron microscopy. At room temperature, a PZT film of 68 ± 2 μm thickness has a relative permittivity of 477 ± 13 and ~ 9,500 at TC = 405oC, showing typical dielectric properties.